Prevalence and Evolution of Susceptibility‐Weighted Imaging Lesions in Patients With Artificial Heart Valves - Philipe S. Breiding; Jana T. Duerrenmatt; Felix G. Meinel; Thierry Carrel; Florian Schönhoff; Felix Zibold; Johannes Kaesmacher; Jan Gralla; Thomas Pilgrim; Simon Jung; Urs Fischer; Marcel Arnold; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2019)
Background In patients with mechanical heart valves, cerebral susceptibility‐weighted imaging (SWI) lesions on magnetic resonance imaging, postulated to be caused by degenerative metallic abrasion, are frequently referred to as valve abrasion. It remains unclear whether valve implantation not requiring cardiopulmonary bypass or biological heart valves also shows those lesions. Methods and Results Two blinded readers rated SWI lesions and cerebral amyloid angiopathy probability according to established criteria on brain magnetic resonance imaging pre‐ and postinterventionally. We assessed the association between valve type/cardiopulmonary bypass use and SWI lesion count on the first postinterventional scan using multivariable logistic regression. On postinterventional magnetic resonance imaging, 57/58 (98%) patients with mechanical heart valves had at least 1 and 46/58 (79%) 3 or more SWI lesions, while 92/97 (95%) patients with biological heart valves had at least 1 and 72/97 (74%) 3 or more SWI lesions. On multivariate analysis, duration of cardiopulmonary bypass during implantation significantly increased the odds of having SWI lesions on the first postinterventional magnetic resonance imaging (β per 10 minutes 0.498; 95% CI, 0.116–0.880; P=0.011), whereas valve type showed no significant association (P=0.338). Thirty‐seven of 155 (23.9%) patients fulfilled the criteria of possible/probable cerebral amyloid angiopathy. Conclusions SWI lesions in patients with artificial heart valves evolve around the time point of valve implantation and the majority of patients had multiple lesions. The missing association with the valve type weakens the hypothesis of degenerative metallic abrasion and highlights cardiopulmonary bypass as the main risk factor for SWI occurrence. SWI lesions associated with cardiac procedures can mimic cerebral amyloid angiopathy. Further research needs to clarify whether those lesions are associated with intracranial hemorrhage after intravenous thrombolysis or anticoagulation.